The Effect of Service Quality on Corporate Reputation and ServicePurchase Decisions at Fun Creative Organizer in Pekanbaru City - Azza Ayumi; Jushermi Jushermi; Agnes Alvionita (West Science Business and Management, 2025)
This study aims to determine the effect of service quality on corporatereputation and service purchase decisions at Fun Creative Organizerin Pekanbaru City. The population in this study consists of all clientswho have used the services of Fun Creative Organizer within the pastyear. The research utilized a proportional stratified random samplingmethod with a total of 100 respondents, including 70 individualclients and 30 institutional or organizational clients. The data wereanalyzed using the Structural Equation Modelling–Partial LeastSquares (SEM-PLS) technique with SmartPLS version 4.1.1.4. Theresults reveal that service quality has a positive and significant effecton both corporate reputation and purchase decisions. Furthermore,corporate reputation significantly mediates the relationship betweenservice quality and purchase decisions. These findings emphasize theimportance of maintaining superior service quality to strengthenreputation and enhance client purchase decisions in the competitiveevent management industry